Plug-in PHP : 100 power solutions - Nixon, Robin , 1961- (McGraw-Hill, 2010)
This practical guide gives you 100 ready-to-run PHP functions for solving most of the main problems you encounter when building a dynamic website with PHP. --from publisher description